From Online to Offline and Vice Versa: Change in Internet Use in Later Life Across Europe - König, Ronny; Seifert, Alexander (Frontiers in Sociology, 2020)
The internet can be a valuable source of social participation in modern society. Although increasing numbers of older adults use the internet, numerous older adults also stop using the internet and become “offliners”. The question of which factors in usage change (i.e., becoming an offliner and vice versa) are most influential remains unclear. This study investigates changes in internet use among the older European population using two waves of representative panel data for 13 countries from the Survey of Health, Ageing and Retirement in Europe (SHARE). The analyses were based on 34,149 respondents aged 50 years and older. In general, the results indicate a positive trend by a slight (2%) increase, from 51% in 2013 to 53% in 2015, although the results also show that a total of 6% stopped using the internet over that time. Our multilevel results suggest that both the onset of and the stoppage of internet usage are driven by changes in socio-economic resources (income and retirement), health resources (subjective health and grip strength), living situation (via relocation), and social factors (partnership and distance to children) as well as in contextual factors such as country-specific wealth and social indexes and internet infrastructure. The study underlines the importance of investigating the influencing factors for starting internet usage and of determining which factors lead to internet stoppage.